2018
DOI: 10.12955/cbup.v6.1277
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Health-Related Quality of Life in Adult Patients With Celiac Disease

Abstract: Objective: This study evaluated the effect of nutrition on health-related quality of life in adult celiac patients.Material-Methods: A total of 103 individuals (26 males and 77 females) diagnosed with celiac disease by a physician, registered in the Ankara Celiac Society, and between 20 and 50 years old were enrolled in the study. Research data was collected using the face-to-face survey method with the “Celiac Disease in Health-Related Quality of Life Survey” to evaluate participants’ quality of life. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A study conducted in Turkey showed that the daily energy intake was lower in celiac patients than in healthy people. 19 Insufficient energy intake also can be a sign of poor food intake. Similarly, it was found in our study that the energy and carbohydrate and dietary fiber intake of both GFD and NGFD groups were lower than the reference values.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Turkey showed that the daily energy intake was lower in celiac patients than in healthy people. 19 Insufficient energy intake also can be a sign of poor food intake. Similarly, it was found in our study that the energy and carbohydrate and dietary fiber intake of both GFD and NGFD groups were lower than the reference values.…”
Section: Discussionmentioning
confidence: 99%